2005
DOI: 10.1097/01.inf.0000172934.98865.14
|View full text |Cite
|
Sign up to set email alerts
|

Chlorhexidine-Impregnated Dressing for Prevention of Colonization of Central Venous Catheters in Infants and Children

Abstract: The chlorhexidine gluconate-impregnated sponge is safe and significantly reduces the rates of CVC colonization in infants and children after cardiac surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
113
4
7

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(135 citation statements)
references
References 27 publications
9
113
4
7
Order By: Relevance
“…Levy et al [7] investigated 166 infants and children between 0 and 18 years from a cardiac intensive care unit. The mean catheterization duration was given with 4.5 days, and follow-up data were missing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Levy et al [7] investigated 166 infants and children between 0 and 18 years from a cardiac intensive care unit. The mean catheterization duration was given with 4.5 days, and follow-up data were missing.…”
Section: Discussionmentioning
confidence: 99%
“…BioPatch® (Ethicon, Norderstedt, Germany) is a chlorhexidineimpregnated sponge (2.5 cm diameter) which can be placed over the CVC insertion site and is covered by a transparent polyurethane dressing. There have been favourable results in paediatric patients undergoing CVC insertion regarding the rates of catheter tip colonization [6,7]. A randomized study of 33 individuals did not reveal a decrease in catheter tip colonizations and CVC-related infection [8].…”
Section: Introductionmentioning
confidence: 99%
“…8 In paediatric patients, two small RCTs found a reduction in catheter colonisation but not CR-BSI, and evidence of localised contact dermatitis when used for infants of very low birth weight. 12,13 We identified one further systematic review and meta-analysis, undertaken as part of a quality improvement collaborative, which synthesised the effects of the routine use of 2% chlorhexidine gluconate (CHG) impregnated sponge dressings in reducing centrally inserted CR-BSI. 14 Five studies were included in the analysis, two of the five studies were in patients in haemo/oncological intensive care units (ICU), the remaining three were in surgical and medical ICU; four of the five studies were sponsored by the manufacturer of the product.…”
Section: Choose the Right Dressing For Insertion Sites To Minimise Inmentioning
confidence: 99%
“…Studies by Garland et al (2001); Levy et al (2005) and Onder et al (2009) specifically evaluated pediatric patients, each of which evaluated the effectiveness of chlorhexidine-impregnated discs versus no discs. Garland et al (2001) performed a prospective, randomized, controlled, multicenter study, which evaluated critically ill neonates requiring a CVC at least 48 hours (n = 705).…”
Section: Effectiveness Of Chlorhexidine-impregnated Discs In Hospitalmentioning
confidence: 99%
“…This study was unique in that the mean duration of catheterization was 17 days, meaning that the use of chlorhexidineimpregnated discs may not be effective in long-term catheterization. Levy and colleagues (Levy et al, 2005) performed a randomized controlled trial in critically ill pediatric patients (n = 145) post-cardiac surgery. This study demonstrated significant reductions in catheter colonization (14.2% reduction, p = 0.04), but no reduction in CRBSIs in the chlorhexidine-impregnated disc group (p = 1).…”
Section: Effectiveness Of Chlorhexidine-impregnated Discs In Hospitalmentioning
confidence: 99%